Comparative assessment of canal transportation, dentin loss, and remaining root filling material by different retreatment files - An In vitro cross-sectional study - Afzal Ali; Prahlad Saraf; Laxmikant Kamatagi; Sandhya Khasnis (Wolters Kluwer Medknow Publications, 2021)
Aim: The purpose of this study was to evaluate the centering ability, canal transportation and efficacy of re-treatment rotary and hand files in removing Gutta Percha from root canals using Cone Beam Computed Tomography(CBCT). Materials and Methods: Sixty extracted human maxillary anteriors were obturated and randomly divided into three groups. Root fillings were removed with ProTaper Universal retreatment system, R-Endo system, and Hedstrom files. CBCT scans were taken. Statistical Analysis and Results: The data were analyzed using the Statistical Package for the Social Sciences (SPSS 15.0, IBM). The mean and standard deviation among the groups was calculated by one-way analysis of variance, Kruskal-Wallis, and Mann- Whitney U-tests, and the comparison among the various groups was done by post hoc Tukey's test. A statistically significant amount of remaining root canal filling material and canal transportation was noted (P < 0.05). Conclusion: No system completely removed the root filling material from root canals. Manual instrumentation resulted in more dentin loss and canal transportation than rotary file system.